Functional Role of Suprahyoid Muscles in Bolus Formation During Mastication - Sasa, Anna; Kulvanich, Sirima; Hao, Naohito; Ita, Reiko; Watanabe, Masahiro; Suzuki, Taku; Magara, Jin; Tsujimura, Takanori; Inoue, Makoto (Frontiers in Physiology, 2022)
It still remains unclear how the suprahyoid muscles function in bolus formation during mastication. This study aimed to investigate the contributory role of the suprahyoid muscles during mastication. A total of 20 healthy young volunteers were asked to perform tongue pressure generation tasks and unilateral mastication tasks using peanuts and two different types of rice crackers. Surface electromyographic (EMG) activity of the masseter and suprahyoid muscles and mandibular kinematics were recorded. Suprahyoid activity increased with increasing tongue pressure. Masticatory duration until the first deglutition differed significantly among the different foods; the harder the food, the longer the duration. This was also the case in masseter activity per masticatory cycle. Masticatory rate and suprahyoid activity per masticatory cycle were significantly higher during soft rice cracker mastication. Masseter activity was higher on the masticatory side than on the non-masticatory side, however, there was no difference in suprahyoid activity between the sides. Suprahyoid activity and jaw gape showed significant positive correlation in the early stage on both the masticatory and non-masticatory sides. The suprahyoid muscles functioned dominantly for jaw-opening during peanut mastication, and for bolus formation, especially in the late stage during soft rice cracker mastication. Bolus formation was performed dominantly on the masticatory side during rice cracker mastication. These findings clearly demonstrate a functional role of the suprahyoid muscles during mastication of solid foods from assessments using both EMG activity and mandibular kinematic recordings.